Inverse analysis on two geotechnical works: a tunnel and a cavern - Eclaircy-Caudron, S. (2007)
One of the major difficulties for geotechnical engineers during project phase is to estimate in a reliable way the mechanical parameters values of the adopted constitutive model. In project phase, they can be evaluated by laboratory and in situ tests. But, these tests lead to uncertainties due to the soil reworking and to local character of the test which is not representative of the soil mass. Moreover for in situ tests interpretation difficulties exist due to the non homogeneous character of the strain and stress fields applied to the soil mass. In order to reduce these uncertainties, geotechnical engineers can use inverse analysis processes during construction. This article shows the application of two of these processes (a deterministic and a probabilistic method) on convergence leveling measurements realized during the excavation of the Bois de Peu tunnel (France). Moreover, these two processes are also applied on displacements measured by inclinometers during the excavation of the hydroelectric powerhouse cavern Venda Nova II (Portugal). The two inverse analysis methods are coupled with two geotechnical software (CESAR-LCPC and FLAC3D) to identify soil parameters. Numerical and experimental results are compared.